Address by Pennsylvania Govenor Milton J. Shapp before the California Democratic Convention - Milton J. Shapp:::::: (1975)
This January 25, 1975 address by Pennsylvania Governor Milton J. Shapp to the California State Democratic Convention argues that Democratic success in 1976 will require party unity, strong organization, and bold economic programs. Shapp criticizes President Ford's economic and energy policies, especially cuts to social programs and proposals favoring defense spending and corporate profits, warning they would deepen recession and inflation. He advocates renewed public sector investment in education, transportation, cities, and job creation—modeled on Kennedy-era policies—as the path to economic recovery and national growth, urging Democrats to lead with a forward-looking program for 1976.